Analisis Pelaksanaan Fungsi Pengawasan Inspektorat Daerah Terhadap Dana Desa Pasar Lapan Kecamatan Air Putih Kabupaten Batubara - Heri, Rusian; Nasution, M. Arif; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
The research objective was to analyze the implementation of the supervisory function of the Inspectorate of the regional funds of the Pasar Lapan village, Air Putih District, Batubara Regency. Obstacles in the implementation of the supervisory function of the Inspectorate of the village funds, Pasar Lapan, Air Putih District, Batubara Regency. The research method used is descriptive with qualitative analysis. Data collection is obtained from interviews, documentation and observation. The result of the research is that supervision or regular inspection of almost all findings in village government has the same problem, the lack of human resources of village government officials. The Pasar Lapan Village Government has carried out in accordance with the procedures set by the government. So that the participation and supervision carried out by the Inspectorate of Batubara Regency has been carried out well. In each Irban regarding special supervision or examination, it is said that in the sale of each Irban consisting of Irban I-Irban IV, special inspection or supervision is subject to a Village Government Administration Report (LPPD) and Village Government Financial Report (LKPD).